Effectiveness Of Repair Material Using Polypropylene Fiber - Zafri Ayob; Ayop, Sallehuddin Shah (Journal of Structural Monitoring and Built Environment, 2025)
The study investigated the impact of polypropylene fiber on the properties of SikaGrout®-215 mortar, focusing on compressive and flexural strength. Tests were conducted on mortar samples with a characteristic strength of 65-70 N/mm2 at 28 days. Polypropylene fiber volume fractions of 0.1%, 0.3%, and 0.5% were examined, with a control mix having no fiber. Surprisingly, fiber addition had no positive effect on compressive strength but significantly increased flexural strength. The addition of fiber increased pore structure, permeability, and porosity, although these decreased with longer curing periods. Despite falling within the range of good quality, the optimal mixture design was observed with a 0.3% fiber combination.